1983
DOI: 10.1021/bi00276a021
|View full text |Cite
|
Sign up to set email alerts
|

Affinity labeling of nicotinamide adenine dinucleotide-dependent isocitrate dehydrogenase by the 2',3'-dialdehyde derivative of adenosine 5'-diphosphate. Evidence for the formation of an unusual reaction product

Abstract: Modification of the pig heart NAD-dependent iswitrate dehydrogenase by the 2',3'-dialdehyde derivative of ADP (oADP) resulted in a time-dependent inactivation of the enzyme. Two kinetically distinct phases are observed for the loss in enzymatic activity with maximum rate constants of 0.38 and 0.023 min-', at saturating concentrations of oADP, at pH Abbreviations: oADP, 2',3'-dialdehyde derivative of ADP; Pipes, piperazine-N,N'-bis(2-ethanesulfonic acid); oATP, 2',3'-dialdehyde derivative of ATP; ACS, aqueous c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

1983
1983
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…Neither the presence of NaBHXN (5 mM), a selective reducing agent of Schiff bases [21], during incubation with the oAdN, nor the addition of NaBH4 (10 mM) after incubation, was necessary for inactivation of ATPase. This was also shown for the inactivation of pyruvate kinase and NADisocitrate dehydrogenase by oAdN [22,23], and beef heart ATPase [lo]. All our experiments were carried out at pH 8.0 since inactivation was about 3-times faster at this pH than at neutral pH.…”
Section: Kinetics Of Inactivation Of Fl By Oadnsupporting
confidence: 65%
“…Neither the presence of NaBHXN (5 mM), a selective reducing agent of Schiff bases [21], during incubation with the oAdN, nor the addition of NaBH4 (10 mM) after incubation, was necessary for inactivation of ATPase. This was also shown for the inactivation of pyruvate kinase and NADisocitrate dehydrogenase by oAdN [22,23], and beef heart ATPase [lo]. All our experiments were carried out at pH 8.0 since inactivation was about 3-times faster at this pH than at neutral pH.…”
Section: Kinetics Of Inactivation Of Fl By Oadnsupporting
confidence: 65%
“…The oxidation of nucleotides by periodate yields 2′,3′‐dialdehyde derivatives that are capable of reacting with lysine residues [21,24]. The present studies showed that the 2′,3′‐dialdehyde derivative of ADP reacts specifically with C. boidinii formate dehydrogenase exhibiting the characteristics of an affinity label for the nucleotide binding site of the enzyme [21,24,35–40]. The inactivation of FDH by oADP obeyed saturation biphasic kinetics that indicates that the oADP forms a dissociable complex with the enzyme prior to covalent modification [22–24,34].…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, oCTP and not contaminating anhydro-oC are responsible for most of the inactivation. Others have demonstrated this type of enzyme accelerated b-elimination reaction with radioactively labeled dialdehyde nucleotides~Lowe & Beechey, 1982; King & Colman, 1983!. Some studies using periodate oxidized nucleotides have provided evidence that the covalent modification proceeds by formation of a Schiff base while others have indicated that a morpholino structure is formed~Hansske et al, 1974; Gregory & Kaiser, 1979;Lowe & Beechey, 1982;King & Colman, 1983, 1990Mas & Colman, 1983;Rayford et al, 1985;White & Levy, 1987;Colman, 1990!. Morpholino derivatives are fairly stable under moderate conditions, but harsher treatment releases or degrades the modifi- peaks at m0z 1,759.8 and 1,761.8 with a single major prompt fragment at m0z 1,650.7.…”
Section: Discussionmentioning
confidence: 99%